A comparison of price-cap and light-handed airport regulation with demand uncertainty. (March 2015) - Yang, Hangjun; Fu, Xiaowen
Highlights: Ex ante price-cap airport regulation is compared with ex post light-handed regulation. Neither regulation dominates in terms of welfare, airport charge or service quality. Average cost pricing may not be optimal due to possible sub-optimal quality. Regulatory regime should be assessed with a comprehensive welfare analysis. Abstract: This study analytically compares the performance of ex ante price-cap airport regulation vs. ex post light-handed airport regulation in the presence of demand uncertainty. Our modeling results suggest that light-handed regulation is a promising method which may lead to higher welfare than price-cap regulation. However, neither regulation strictly dominates the other in terms of welfare, airport charge or service quality. The relative performance of alternative regulations depends on many market factors and the specification of penalty under light-handed regulation. Our analytical results also suggest that if service quality matters and if an airport is allowed to invest in a higher quality, average cost pricing may not be optimal due to possible sub-optimal choices of quality, and the overall performance of alternative regulatory regimes should be assessed with a comprehensive welfare analysis. Our investigation confirms that light-handed regulation is worth preserving subject to monitoring and continuous improvements.